Illuminating the Prevalence of Trypanosoma brucei s.l. in Glossina Using LAMP as a Tool for Xenomonitoring. - Lucas J Cunningham; Jessica K Lingley; Lee R Haines; Joseph M Ndung'u; Stephen J Torr; Emily R Adams (PLoS Neglected Tropical Diseases)
Background As the reality of eliminating human African trypanosomiasis (HAT) by 2020 draws closer, the need to detect and identify the remaining areas of transmission increases. Here, we have explored the feasibility of using commercially available LAMP kits, designed to detect the Trypanozoon group of trypanosomes, as a xenomonitoring tool to screen tsetse flies for trypanosomes to be used in future epidemiological surveys. Methods and findings The DNA extraction method was simplified and worked with the LAMP kits to detect a single positive fly when pooled with 19 negative flies, and the absolute lowest limit of detection that the kits were able to work at was the equivalent of 0.1 trypanosome per ml. The DNA from Trypanosoma brucei brucei could be detected six days after the fly had taken a blood meal containing dead trypanosomes, and when confronted with a range of non-target species, from both laboratory-reared flies and wild-caught flies, the kits showed no evidence of cross-reacting. Conclusion We have shown that it is possible to use a simplified DNA extraction method in conjunction with the pooling of tsetse flies to decrease the time it would take to screen large numbers of flies for the presence of Trypanozoon trypanosomes. The use of commercially-available LAMP kits provides a reliable and highly sensitive tool for xenomonitoring and identifying potential sleeping sickness transmission sites.